Phenotypic and genotypic characterisation of invasive Streptococcus pneumoniae expressing atypical capsular types - Mokupi, Rethabile (Department of Molecular and Cell Biology, 2022)
Abstract Background: Streptococcus pneumoniae (pneumococcus) is one of the leading causes of morbidity and mortality. It accounts for over 500 000 case fatalities in children annually. Its invasive nature is not well understood; however, progress has been made with the discovery of the major virulence factor: the polysaccharide capsule. The biochemical properties of the capsule have allowed for the identification of more than 100 serotypes, resulting in the development of new, effective vaccines. However, in recent years, it has become challenging to identify serotypes, due to mutations in the capsular gene cluster of atypical isolates. The encoded capsules have been shown to cross react with anti-sera from other pneumococcal serogroups. We, therefore, aimed to phenotypically and genotypically characterise a subset of isolates collected from a nationwide surveillance program, exhibiting atypical serotyping results. Methods: A convenient sample of 68 atypical isolates were selected for the purpose of this study. Pneumococci were isolated and characterized using conventional microbiological laboratory techniques. Confirmed pneumococci were then subjected to antimicrobial susceptibility testing using the Kirby Bauer disk diffusion method and serotyped using the Quellung method. Genotypic characterization was conducted by analysing whole-genome sequencing data to reveal the in-silico serotype, multi-locus sequence type profiles, virulence factors, and antibiotic-resistance genes present, including whole genome sequencing-inferred minimum inhibitory concentration where applicable. Analysis of the capsular loci for single nucleotide polymorphism mutations were also conducted. Nuclear magnetic resonance was used to characterise the pneumococcal polysaccharide capsule. Results: Of all the pneumococci included in this study, 21% (14/68), 7% (5/68), 6% (4/68), 1% (1/68) of the isolates were resistant to tetracycline, chloramphenicol, azithromycin, and cefuroxime, respectively. Only 11% of the isolates were resistant to more than one drug. A total of 24 Sequence types (ST) were identified amongst the isolates. Ten of the isolates were identified as novel STs, and were thus assigned a unique ST. Among the 14 known STs, 12 have been known to be associated with invasive encapsulated pneumococci. ST9813 was the most prevalent ST. All isolates belonged to serogroup 35 (35A, 35B, 35C and 35F). The majority of isolates were primarily identified as serotype 35B, 72% (49/68) vs 59% (40/68) for the Quellung reaction and whole genome sequencing, respectively. Analysis of the capsular loci revealed the presence of 146 non-synonymous mutations in the capsule encoding biosynthetic genes. Nuclear magnetic resonance data was inconclusive, although electron microscopy revealed the presence of the polysaccharide capsule. Conclusions: Comparative genomics analysis revealed single nucleotide polymorphism mutations in the capsular biosynthetic genes, that may alter the production of the polysaccharide capsule; resulting in atypical behaviour observed within these strains. A high concordance rate between phenotypic and molecular tests was observed, and the utilization of both methods allowed for a detailed investigation of atypical pneumococcal isolates. There is a need for continued surveillance of atypical strains and optimisation of pneumococcal capsular extraction protocols, to further elucidate the chemical structure of these novel atypical strains of pneumococci.